PENERAPAN MODEL KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR IPS TENTANG CUACA PADA SISWA KELAS III SEKOLAH DASAR - Nurohmah, Fatia; Susiani, Tri Saptuti; Salimi, Moh (LPPM Universitas Bina Bangsa, 2023)
The study aimed to describe the steps for implementing the make a match, improve social science learning outcomes through the implementation of make a match, and describe the constraint and solution in learning. It was collaborative classroom action research. The subjects were teacher and 32 students of third grade consisting of 11 boys and 12 girls. The data were qualitative and quantitative. Data collection techniques were observation, interviews, and test. Data validity used triangulation of sources and triangulation of techniques. Data analysis included data reduction, data presentation, and drawing conclusionsThe results indicated that the implementation of make a match improved social science learning outcomes. The passing grades were 73.91% in the first cycle, 82.61% in the second cycle, and 91.30% in the third cycle. The averages of student’s score in the first cycle were 72.61 (first meeting) and 80.65 (second meeting). The scores in the second cycle were 77.39 (first meeting) and 81.09 (second meeting) while the third cycle was 85.65. The obstacle was managing the students in searching the partner cards. It concludes that the implementation of Make a Match improves science learning outcomes about the weather to third grade students